2014
DOI: 10.1177/0300060513503926
|View full text |Cite
|
Sign up to set email alerts
|

Low expression of insulin-like growth factor binding protein 7 associated with poor prognosis in human glioma

Abstract: Objectives: To investigate insulin-like growth factor binding protein 7 (IGFBP7) mRNA levels in human glioma and normal brain tissue, and to determine their clinical significance. Methods: In this retrospective study, IGFBP7 mRNA was quantified by real-time reverse transcription-polymerase chain reaction in brain tissue samples from patients with glioma and normal control subjects. Kaplan-Meier and Cox proportional hazards analyses were performed to determine any clinical and prognostic associations. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
2
6
1
Order By: Relevance
“…Thus, according to our results and consistent with the research conclusions reported, TMEM149 and EVI2B are required further study with corresponding tumor types to find better prognostic biomarkers. In addition, we found 74 other immune-related genes with a significant prognostic role for at least one tumor type, some of which have been reported by previous studies ( 49 52 ). Overall, these results suggest new possibilities for immune-related prognostic biomarkers, but further experimental and functional studies urgently need to be carried out to validate their predictive roles.…”
Section: Discussionsupporting
confidence: 81%
“…Thus, according to our results and consistent with the research conclusions reported, TMEM149 and EVI2B are required further study with corresponding tumor types to find better prognostic biomarkers. In addition, we found 74 other immune-related genes with a significant prognostic role for at least one tumor type, some of which have been reported by previous studies ( 49 52 ). Overall, these results suggest new possibilities for immune-related prognostic biomarkers, but further experimental and functional studies urgently need to be carried out to validate their predictive roles.…”
Section: Discussionsupporting
confidence: 81%
“…It regulates some genes (including insulin-like growth factor 2, -actin and-transduction proteins) translation by binding to their mRNA. Some studies [55,56] found that IGFBP subtype has become a biomarker for diagnosis and prognosis of astrocytomas. IGF2BP3 was identified as a GBM-specific proliferative and pre-invasive marker that activates the oncogene PI3K and MAPK pathways through the action of IGF-2 [57].…”
Section: Discussionmentioning
confidence: 99%
“…Tian et al found that IGFBP7 mRNA levels were substantially decreased in human glioma in comparison to healthy brain tissue (110) and that low levels of IGFBP7 mRNA were associated with larger tumor size, and patients with higher IGFBP7 expression had longer overall survival. Pen et al (111) described that IGFBP7 acts as a tumor suppressor by lowering glioblastoma cell growth and inducing senescence, although not programmed cell death (111).…”
Section: Igfbp7 With Mesenchymal Tumors Gliomamentioning
confidence: 99%